(untitled) (Journal of Global Accounting, 2025)
This study examined the influence of corporate governance mechanisms on the financial reporting quality (FRQ) of listed manufacturing firms in Nigeria from 2015 to 2022. Employing agency theory as its theoretical underpinning, the research investigated six governance variables namely board size, and board independence. Financial reporting quality is measured using discretionary accruals derived from the Modified Jones Model. The study adopted a robust quantitative methodology, analyzing secondary data from the annual reports of 49 manufacturing firms. Diagnostic tests, including heteroskedasticity, multicollinearity, mis-specification, and normality assessments, ensure the reliability of the regression results. Key findings revealed that board size negatively and significantly impacts FRQ. In contrast, board independence demonstrated insignificant effects, with varying directional influences. To address outliers and enhance model robustness, robust regression techniques were employed. The results emphasized the critical role of optimizing board composition and leveraging foreign ownership to enhance transparency and accountability in financial reporting. This study contributes to the ongoing discourse on corporate governance in emerging economies, offering valuable insights for policymakers, practitioners, and stakeholders in the manufacturing sector. Recommendations include fostering regulatory frameworks that support balanced board structures, enhancing gender diversity, and attracting foreign investment to align corporate practices with global governance standards. By addressing governance challenges, this research underscores the potential for improved financial reporting quality to promote investor confidence and economic stability in Nigeria.